Analisis Determinan Profitabilitas Bank Umum Syariah di Indonesia - Maulidya Annisa; Yayuk Sri Rahayu (INSTITUT AGAMA ISLAM SEBI, 2026)
The objective of this research is to investigate how economic freedom, economic growth, inflation, the capital adequacy ratio (CAR), and non-performing financing (NPF) influence the profitability of Islamic Commercial Banks (ICB) in Indonesia from 2015 to 2024. This research employs a quantitative approach, using panel data regression analysis in Eviews 12. The population consists of Islamic Commercial Banks registered with the Financial Services Authority (OJK) in Indonesia. The data period is from 2015 to 2024 with a total of 14 ICBs. Eight Islamic Commercial Banks were obtained using purposive sampling. The findings of this study indicate that economic freedom has a positive effect on the profitability of Islamic Commercial Banks, while non-performing financing (NPF) has a negative effect. The profitability of Islamic Commercial Banks is not significantly influenced by factors such as economic growth, inflation, and capital adequacy ratio (CAR). Therefore, Islamic Commercial Banks need to prioritize strict financing risk management to control non performing financing (NPF) and continue to implement policies that increase economic freedom to improve their profitability. Tujuan dari penelitian ini adalah untuk menyelidiki bagaimana kebebasan ekonomi, pertumbuhan ekonomi, inflasi, rasio kecukupan modal (CAR), dan pembiayaan bermasalah (NPF) memengaruhi profitabilitas Bank Umum Syariah (BUS) di Indonesia sejak tahun 2015 hingga 2024. Penelitian ini menggunakan pendekatan kuantitatif, yakni menggunakan analisis regresi data panel dengan memanfaatkan perangkat lunak Eviews 12. Populasi yang digunakan terdiri dari BUS di Indonesia yang terdaftar di Otoritas Jasa Keuangan (OJK) untuk periode 2015 sampai dengan 2024, berjumlah total 14 BUS. Delapan BUS diperoleh dengan menggunakan purposive sampling. Temuan penelitian menunjukkan bahwa kebebasan ekonomi berpengaruh positif terhadap profitabilitas BUS, sedangkan pembiayaan bermasalah (NPF) memiliki pengaruh negatif. Profitabilitas BUS tidak dipengaruhi secara signifikan oleh faktor-faktor pertumbuhan ekonomi, inflasi, dan rasio kecukupan modal (CAR). Oleh sebab itu, BUS perlu memprioritaskan pengelolaan risiko pembiayaan yang ketat untuk mengendalikan pembiayaan bermasalah (NPF) dan terus memanfaatkan kebijakan yang meningkatkan kebebasan ekonomi guna meningkatkan kinerja profitabilitas mereka.